Absolute Configurations of Four Resorcylic Acid Lactones, Paecilomycins J − M, by CD/TDDFT Calculations. Issue 1 (26th November 2013) - Xu, Liang‐Xiong; Xue, Jing‐Hua; Wu, Ping; You, Xiao‐Ying; Wei, Xiao‐Yi
ABSTRACT The absolute configurations of four resorcylic acid lactones (RALs), paecilomycins J − M (1, 2, 3 and 5), were assigned by Time‐Dependent Density‐Functional Theory (TDDFT) calculations of their electronic circular dichroism (CD) spectra. The previously reported structure 4 for paecilomycin M was found to be incorrect and should be changed to structure 5. Analysis of structure‐spectrum relationship for this group of RALs suggested that V′‐shape conformations give type I CD spectra (two negative Cotton effects around 300 and 260 nm, a positive Cotton effect around 220 nm) while V‐shape conformations yield type II spectra (signs of three Cotton effects were opposite to those in type I). Chirality 26:44–50, 2013. © 2013 Wiley Periodicals, Inc.